Carbohydrate availability and muscle energy metabolism during intermittent running - Foskett, A.; Williams, C.; Boobis, L.; Tsintzas, K. (Medicine & Science in Sports & Exercise, 2008)
Purpose: To examine the influence of ingesting a carbohydrate-electrolyte (CHO-E) solution on muscle glycogen use and intermittent running capacity after consumption of a carbohydrate (CHO)-rich diet.